If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 1(8x + 12) = 0 Reorder the terms: 6 + 1(12 + 8x) = 0 6 + (12 * 1 + 8x * 1) = 0 6 + (12 + 8x) = 0 Combine like terms: 6 + 12 = 18 18 + 8x = 0 Solving 18 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 8x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 8x = 0 + -18 8x = 0 + -18 Combine like terms: 0 + -18 = -18 8x = -18 Divide each side by '8'. x = -2.25 Simplifying x = -2.25
| X-366=314 | | 90=n+n-10 | | 11x-5-6x=6x-2 | | 2x+y=10x+90 | | x(3x+54)(2x)=360 | | -8+6x=2x+16 | | X=4x-3x-10 | | -30+-80= | | 11x-(2x-5)=32 | | 10x+4=12x-15 | | -.72x=-1.44 | | X-6x=-35 | | 6(5-8w)+12=54 | | 71+(-71)= | | 4(-3-y)-3(-3)=-7 | | 4(1x-6)+4=6x-6 | | 4x+6x-60=45-5x | | 90=x+13+x | | -11x-9=-64 | | 2(b+2)=-4(b+7)-2b | | 48=32-2(x-3) | | -5(1+6b)=-8b+36 | | P^3+57=q^2 | | Q=12 | | 4x=6x-34 | | 25+(-20)= | | 20+3y=y+21-2y | | -[8z-(19z+10)]=10+(10z+5) | | x^2-6x+y^2+2y-15=0 | | 1=-0.5B+B | | 17-18k=-15 | | 8m-6=m+8 |